An Efficient Ultrasound Promoted Three‐Component and Regioselective Synthesis of Indenoquinoxaline Compounds Containing Pyrrolopyrimidine Skeleton. Issue 15 (17th April 2019) - Alizadeh, Abdolali; Ghasemzadeh, Hossein; Roosta, Atefeh; Halvagar, Mohammad Reza
Abstract: A series of new indeno[1, 2‐ b ]quinoxaline compounds containing pyrrolopyrimidine skeleton have been synthesized in excellent yields using an improved and efficient synthetic methodology under ultrasonic irradiation in the absence of any added catalyst. The reactions were carried out under both thermal and ultrasonic irradiation condition. In general, obvious improvement in reaction time and milder conditions were observed when reactions were carried out under sonication compared with conventional silent conditions. Abstract : A series of indeno[1, 2‐b]quinoxaline compounds containing pyrrolopyrimidine skeleton have been synthesized through the bicyclization strategy, from ninhydrin, phenylenediamine, 1‐phenyl‐2‐(1, 1, 1‐triphenyl‐ λ 5 ‐phosphanylidene)ethan‐1‐one, diamine, and 1, 1‐bis(methylthio)‐2‐nitroethylene. The reactions were carried out under both thermal and ultrasonic irradiation condition. In general, obvious improvement in reaction time and milder conditions were observed when reactions were carried out under sonication compared with conventional silent conditions.